ANALISIS DAMPAK E-LEARNING TERHADAP SIKAP SPIRITUAL SISWA DI SEKOLAH ISLAM - Kurnaesih, Uun; Alimulloh; Diah Nurul Islami; Muhamad Nur Ilham (Ta'dibiya, 2024)
This study aims to examine the impact of e-learning on students' spiritual attitudes in Islamic schools. With the rapid development of technology, e-learning has become an increasingly accepted learning method in various educational institutions. However, it is important to assess how this method affects students' spirituality, which is an essential component of Islamic education. This study uses a qualitative approach with a case study method in several Islamic schools. Data were collected through the method used in this study, namely the library research method. The results of the study indicate that the use of e-learning has a complex impact on students' spiritual attitudes. On the one hand, e-learning allows wider and easier access to learning materials oriented towards spiritual development, such as religious lecture videos, religious e-books, and online discussion forums that enrich students' understanding. In addition, the flexibility of time offered by e-learning can improve students' self-discipline and independence, which are important parts of spiritual attitudes. On the other hand, this study also found significant challenges. The lack of face-to-face interaction can reduce emotional and spiritual closeness between students and teachers, as well as between students themselves. In addition, the presence of digital distractions during online learning can interfere with students' concentration and focus on spiritual development. Therefore, this study emphasizes the importance of a balanced and holistic e-learning implementation strategy to ensure that students' spiritual attitude development remains optimal. Supervision and guidance from teachers and parental involvement are also identified as important factors in supporting this process. This study concludes that e-learning has great potential in supporting students' spiritual attitude development in Islamic schools, but requires a planned and sustainable approach to overcome the various challenges that exist.